Impacto de la instalación de medidores sobre el consumo de agua potable en los hogares de Lima Metropolitana - Álvarez Carcheri, Renzo Antonio (2024)
The goal of this research work is to estimate the impact of the installation of meters on the consumption of drinking water in homes in Metropolitan Lima during the period 2016-2019. The estimation method consists of proposing a panel data quantile regression model with fixed effects that allows capturing the unobservable heterogeneity between households and examining the effect of the meters along different points of the consumption distribution. The results indicate that, in households in the lowest quantiles (0.10 to 0.30), the reduction in consumption is 13% and as we move towards the 0.50 quantile, the effect intensifies, reaching a reduction of 21.5%. These results reinforce the effectiveness of micrometering programs as tools for the sustainable management of water resources in addition to contributing to the financial sustainability of the water company by reducing the levels of non-billed water.